Responsibility of Land Deed Officials in the Making of Sale and Purchase Deeds with Improper Transactions - Amelia Nugroho (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2023)
Before a Land Deed Official make a land sale and purchase deed so that a transfer of rights over land and buildings can arise, he/she must carry out tax payment services by the parties. This is sometimes different from the reality, in which in making a sale and purchase deed the Land Deed Official commits an act of manipulating the tax price to be less than the actual sale and purchase price. The research method used in this legal research is normative. The data used in this legal research is secondary data. The results of research in writing this law are that there are still Land Deed Making Officials in making sale and purchase deeds who openly suggest reducing the value of land transactions to as small as possible for service users with the aim of ensuring that the tax costs paid by the parties are not large. Therefore, the Land Deed Official must bear the sanctions in the form of administrative sanctions, civil sanctions and criminal sanctions.Keywords: Tax Violations, Land Deed Official, Land Sale and Purchase Deed.